Mengapa Kita Perlu Regulasi Penyiaran? - Rochim, Mochamad (FIkom Unisba, 2007)
The rise of media market in Indonesia has obvious impacts in the world of Indonesian media—especially television. There are more than 11 national commercial televisions, and hundreds of local television today—thanks for SK Menteri Penerangan Th. 111/1990 which allowing mass media business to be operated in Indonesia. But, years after such liberalizations, televisions has growing rapidly without real regulations. Complaints come from citizens concerning the low quality of TV programs, the tendency of mono-culturalization, and unhealthy market (and content) due to monopolistic ownership. These complaints marked the needs of broadcasting regulation. Based on the assumption frequency as public’s own, therefore, the use of frequencies must be dedicated to educate and serve public needs.